Selecting Sustainable Drainage Structures Based on Ecosystem Service Variables Estimated by Different Stakeholder Groups - Scholz, Miklas; Uzomah, Vincent; Almuktar, Suhad; Radet-Taligot, Julie (Water (Basel), 2013)
In times of recession, expert systems supporting environmental managers undergo a revival. However, the retrofitting of sustainable water structures is currently undertaken ad hoc using engineering experience supported by minimal formal guidance. There is a lack of practical decision tools that can be used by different professions for the rapid assessment of ecosystem services that can be created when retrofitting water structures. Thus the aim was to develop an innovative decision support tool based on the rapid estimation of novel ecosystem service variables at low cost and acceptable uncertainty. The tool proposes the retrofitting of those sustainable drainage systems that obtained the highest ecosystem services score for a specific urban site subject to professional bias. The estimation of variables was undertaken with high confidence and manageable error at low cost. In comparison to common public opinion, statistically significant differences between social scientists and the general public for the estimation of land costs using the non-parametric Mann-Whitney U-test were found. It was also surprising to find no significant differences in the estimation of habitat for species by civil engineers and ecologists. The new methodology may lead to an improvement of the existing urban landscape by promoting ecosystem services.